2021
DOI: 10.1177/09544062211005795
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of functionally graded carbon nanotubes reinforced composite joined spherical-cylindrical-spherical thin-walled structure

Abstract: Functionally graded carbon nanotubes reinforced composite joined spherical-cylindrical-spherical thin-walled structure under the actions of axial and lateral distributed loads is considered. The static buckling of this structure is analyzed numerically. The Ritz method is used to derive the governing equations of the joined thin-walled structure buckling. Higher-order shear deformation theory is applied to describe the structure stress-strain state. The continuity conditions of the spherical-cylinder junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(58 reference statements)
0
1
0
1
Order By: Relevance
“…Тонкостінні конструкції з нанокомпозитних матеріалів, що складаються з конічних та циліндричних оболонок, досліджувалися в роботах [3,5,7,19,22].…”
Section: моделі тонкостінних нанокомпозитних конструкційunclassified
“…Тонкостінні конструкції з нанокомпозитних матеріалів, що складаються з конічних та циліндричних оболонок, досліджувалися в роботах [3,5,7,19,22].…”
Section: моделі тонкостінних нанокомпозитних конструкційunclassified
“…For example, the application of GNPs in control of the dynamic response of the conical shells was investigated in Al-Furjan et al 4 and Keshtegar et al 5 In some other studies, CNTs are employed as the reinforcing phase of the composites. In several studies such as Mohammadimehr et al, 6 Adhikari and Singh, 7 and Avramov et al 8 it has been showed that enrichment of the structures by CNTs leads to enhance of their structural characteristics. In this regard, Shahmohammadi et al 9 developed an analytical solution based on the modified interaction method to investigate the snap-through behavior of CNT-reinforced shallow spherical shells.…”
Section: Introductionmentioning
confidence: 99%